280 GHz receivers for the SPIDER CMB polarimeter - Shaw, Elle Claire (2024)
The SPIDER instrument is optimized to search for a degree-scale B-mode polarization signature in the cosmic microwave background left by primordial gravitational waves. A positive detection of the B-mode signature would provide a window to the early universe and discriminate among inflation models. During its first flight in 2015, SPIDER mapped approximately 10 percent of the sky at 95 and 150 GHz. This dissertation covers the second flight of the SPIDER instrument, from the hardware upgrades and integration through launch and a preliminary analysis of the 280 GHz detector performance. SPIDER's second flight from McMurdo Station, Antarctica, in December 2022-January 2023, deployed over 2,500 detectors distributed across three 280 GHz receivers, two 95 GHz receivers, and one 150 GHz receiver. With the addition of the 280 GHz band, SPIDER is poised to make a state-of-the-art measurement of the Galactic foregrounds that contaminate the cosmological signal. Submission original under an indefinite embargo labeled 'Open Access'. The submission was exported from vireo on 2024-03-01 without embargo terms The student, Elle Shaw, accepted the attached license on 2023-11-03 at 17:44. The student, Elle Shaw, submitted this Dissertation for approval on 2023-11-03 at 18:06. This Dissertation was approved for publication on 2023-11-07 at 14:14. DSpace SAF Submission Ingestion Package generated from Vireo submission #19886 on 2024-03-01 at 13:14:05